Eighth survey of staffing in cardiology in the United Kingdom 1992. Issue 5 (May 1994) - Chamberlain, D.; Parker, J.; Balcon, R.; Webb-Peploe, M.; Cobbe, S.; Boyle, D.; Tynan, M.; Hunter, S.; Reval, K.
Abstract : The Eighth Survey of Staffing in Cardiology was conducted with an index date of 30 September 1992. The total number of cardiologists in England and Wales, defined as individuals trained in the specialty and spending at least 40% of their professional time working in it, was 358. Of these 11 were part time, defined as six sessions or less, giving a number in whole time (or near whole time) equivalents of 352.5. The number of individuals increased from 1991 by 18 (5.3%). There were 71 cardiologists in Scotland and Northern Ireland, making a total for the United Kingdom of 429 individuals (423.5 whole time equivalents), which is 7.3 per million population. A total of 44 Districts serving 8.8 million people have no resident cardiologist. There has been little improvement since the 1991 survey. An additional 34 Districts with populations greater than 250, 000 have only one cardiologist: we have clear evidence of inadequate provision of care in most of these, a situation that is inevitable within the resources provided. A wider threat to the provision of a satisfactory level of cardiological care throughout the United Kingdom will follow from changes in the organisation of the National Health Service and in the new requirements for training of future cardiologists because these changes will make major new demands on consultant time which cannot be met within existing resources. A crisis will be averted only if a rapid and major expansion of the consultant grade can be achieved.